ANALISIS PEMELIHARAAN BERKALA DENGAN KINERJA GENERATOR SET 1600 KVA DI PT. McDERMOTT INDONESIA - Maulana, Alif Sendi (Journal of System Information Technology and Electronics Engineering (J-SITEE); Vol 3 No 1 (2023): JUNI 2023DO - 10.31331/jsitee.v3i1.2653, 2024)
PT. McDermott Indonesia (PTMI) is an offshore construction fabrication company that requires a large and stable power supply. They utilize the main power supply from PLN with a capacity of 6890 KVA for all electronic equipment. Gensets are used as backup power in case of failures or when the power usage exceeds the limit of the main power supply. To ensure the operational availability of the gensets, the company prepares the genset equipment, calculates the availability and usage rates, and assesses the resulting losses. The designated operating time (SOT), total number of failures (T), and routine maintenance time (S) are collected within a specified timeframe. By subtracting the service time, the Actual Operating Time (AOT) of the gensets is obtained. The SOT and AOT data are utilized to calculate the availability rate of the generator set. In 2022, the average reliability rate of the gensets reached 99%, indicating rare occurrences of disruptions, and the availability of the gensets remained uninterrupted.